The Development of an Evaluation Instrument for the Implementation of the Arabic Language Curriculum in Islamic High School - Hamid, Muhammad Abdul; Sutaman, Sutaman; Natsir, Muhammad; Muhammad Salih, Ibnu Omar (Universitas Islam Negeri Raden Intan Lampung, 2022)
In the context of the curriculum in Madrasah (Islamic school), the government has determined the concept, implementation, and evaluation of the curriculum in the Decree of the Minister of Religion (KMA) number 183, 184, and 189. It required to formulate an evaluation instrument in the need of curriculum implementation for the process of curriculum implementation evaluation at the practical level in education units. The purpose of this study was to develop an evaluation instrument of curriculum implementation in the form of a curriculum achievement assessment questionnaire. This study used a Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. In collecting the data, this study used the Dhelpi technique; consultative discussions with experts as validators in the preparation of instruments which included components, aspects, and indicators. FGD (Forum Group Discussion); with Arabic language teachers were applied to analyze the needs related to the development of an evaluation model for curriculum implementation and to formulate aspects of components and indicators of achievement of the Arabic language curriculum. The results showed that the instrument for evaluating curriculum implementation included the formulation of components, aspects, and indicators in the Context, Input, Process, Product, and Outcomes (CIPPO). The components, aspects, and indicators in the CIPPO model were formulated through the conceptual analysis and the contextualization of KMA number 183, 184, 189 and language performance theory as a benchmark and a standard for assessing the achievement of the Islamic high school Arabic curriculum.